2019
DOI: 10.1037/ccp0000386
|View full text |Cite
|
Sign up to set email alerts
|

Sticking it out in trauma-focused treatment for PTSD: It takes a village.

Abstract: Objective-One in three veterans will dropout from trauma-focused treatments for PTSD. Social environments may be particularly important to influencing treatment retention. We examined the role of two support system factors in predicting treatment dropout: social control (direct efforts by loved ones to encourage veterans to participate in treatment and face distress) and symptom accommodation (changes in loved ones' behavior to reduce veterans' PTSD-related distress).Method-Veterans and a loved one were survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
73
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(83 citation statements)
references
References 78 publications
5
73
1
2
Order By: Relevance
“…For example, improving the quality and frequency of social connection may facilitate veterans' engagement in PTSD treatment and response to treatment. This premise is supported by previous research showing that family support for treatment increases veterans' likelihood of staying in treatment (Meis et al, 2019) and that veterans with more social support were less likely to endorse the belief that it is up to them to handle their problems and more likely to seek treatment (Graziano & Elbogen, 2017). Further, family involvement in PTSD care was associated with more PTSD symptom reduction (Laws, Glynn, McCutcheon, Schmitz, & Hoff, 2017), and greater social support predicts better PTSD treatment response (Price, Gros, Strachan, Ruggiero, & Acierno, 2013;Price et al, 2018;Shnaider, Sijercic, Wanklyn, Suvak, & Monson, 2017).…”
Section: Discussionsupporting
confidence: 71%
“…For example, improving the quality and frequency of social connection may facilitate veterans' engagement in PTSD treatment and response to treatment. This premise is supported by previous research showing that family support for treatment increases veterans' likelihood of staying in treatment (Meis et al, 2019) and that veterans with more social support were less likely to endorse the belief that it is up to them to handle their problems and more likely to seek treatment (Graziano & Elbogen, 2017). Further, family involvement in PTSD care was associated with more PTSD symptom reduction (Laws, Glynn, McCutcheon, Schmitz, & Hoff, 2017), and greater social support predicts better PTSD treatment response (Price, Gros, Strachan, Ruggiero, & Acierno, 2013;Price et al, 2018;Shnaider, Sijercic, Wanklyn, Suvak, & Monson, 2017).…”
Section: Discussionsupporting
confidence: 71%
“…Patients are often interested in including loved ones in their PTSD treatment and have been shown to respond to PE more effectively when there are family and peer supports included in their care (Batten et al, 2009;Hundt et al, 2015). Utilizing family or peer support during PE may increase engagement, decrease dropout, and enhance clinical outcomes (Hernandez-Tejada et al, 2017;Meis et al, 2019;Price et al, 2013Price et al, , 2018. For example, Meis et al (2019) found that veterans with loved ones who encouraged them to approach anxiety-provoking situations and sit with their distress rather than avoid it were twice as likely to complete trauma-focused PTSD treatment (e.g., PE or cognitive processing therapy).…”
Section: Utilizing Social Support During Pe In the Midst Of A Pandemicmentioning
confidence: 99%
“…Utilizing family or peer support during PE may increase engagement, decrease dropout, and enhance clinical outcomes (Hernandez-Tejada et al, 2017;Meis et al, 2019;Price et al, 2013Price et al, , 2018. For example, Meis et al (2019) found that veterans with loved ones who encouraged them to approach anxiety-provoking situations and sit with their distress rather than avoid it were twice as likely to complete trauma-focused PTSD treatment (e.g., PE or cognitive processing therapy). If a patient consents, providers may consider meeting with the patient and their social support or supports via CVT after the first session of PE to summarize psychoeducation about PTSD, avoidance, and exposure therapy and provide information about how they can support the patient to engage in approach behaviors rather than collude with avoidance.…”
Section: Utilizing Social Support During Pe In the Midst Of A Pandemicmentioning
confidence: 99%
“…There is increasing recognition of the role of social factors in the development, maintenance, and treatment of PTSD, as evidenced by a keynote address at a recent annual conference of the International Society for Traumatic Stress Studies, entitled “Why Social Factors Matter for Coping with Trauma” (Bryant, 2018). Social support also influences veterans’ engagement in PTSD treatments (e.g., Fredette, El‐Baalbaki, Palardy, Rizkallah, & Guay, 2016; Kehle‐Forbes, Meis, Spoont, & Polusny, 2016; McGinn, Hoerster, Stryczek, Malte, & Jakupcak, 2017; Meis et al., 2019). Indeed, veterans with strong social support networks may receive more encouragement to seek and persist in treatment, whereas those lacking support may not receive such encouragement (Sayer et al., 2009; Spoont et al., 2014).…”
mentioning
confidence: 99%